Transparent-black electrochromic device and preparation method thereof
By using transparent conductive electrodes and discoloration active layer structures in electrochromic devices, combining physical blending methods of cathode and anode electrochromic materials, the electrochromic device structure in the prior art is solved by solving the complex structure and inability to achieve transparent-black switching in the prior art. The problem of this problem has achieved efficient transparency-black switching and excellent cycle stability, expanding its application prospects.
Patent Information
- Application Number
- CN202411419779.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing electrochromic devices have complex structures and are unable to achieve transparent-black switching, which limits their applications in more fields.
The transparent conductive electrode and discoloration active layer structure are adopted to form transparent-black electrochromic devices through physical blending of cathode electrochromic materials, anode electrochromic materials and electrolytes, which simplifies the device structure and processing technology.
It achieves a change from transparent to black, with pure color and excellent cycle stability, and is suitable for smart glasses, rearview mirrors and other fields.
Smart Images

Figure CN119310774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochromic devices, and in particular to a transparent-black electrochromic device and a preparation method thereof. Background Art
[0002] In recent years, electrochromic technology has been widely used in smart windows, rearview mirrors and other fields. However, black electrochromic materials are still a problem in the field of electrochromic. There are usually several methods to achieve transparent-black switching: ① Obtain electrochromic materials with uniform and full absorption in the visible light region through molecular structure design; ② Achieve uniform and full absorption in the visible light region through stacking and compounding of electrochromic materials of different colors; ③ Physically blend electrochromic materials of different colors to achieve color complementarity and achieve uniform and full absorption in the visible light region.
[0003] The electrochromic material is encapsulated in the device through certain process means. At this time, the device has the electrochromic function, so it is called an electrochromic device. After years of development, electrochromic devices have a mature device structure, namely a five-layer sandwich structure. The structure is divided into five layers: conductive substrate layer, electrochromic layer, electrolyte layer, ion storage layer and conductive substrate layer. However, the complex device structure restricts the development of electrochromic devices in more fields. Therefore, the optimization design of electrochromic structure and process is an important research direction in the field of electrochromism. Summary of the invention
[0004] The object of the present invention is to provide a transparent-black electrochromic device and a preparation method thereof, so as to solve the problems in the prior art that the electrochromic device has a complex structure and cannot achieve transparent-black switching.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a transparent-black electrochromic device, which comprises a transparent conductive electrode 1, a color-changing active layer, and a transparent conductive electrode 2 which are arranged in sequence;
[0007] The color-changing active layer comprises a cathode electrochromic material 1, a cathode electrochromic material 2, an anode electrochromic material and an electrolyte.
[0008] Preferably, the cathode electrochromic material 1 has a structure as shown in formula (I):
[0009]
[0010] Among them, X 1 - Selected from I - Br - , Cl- , ClO 4 - , BF 4 - PF 6 - or TFSI - , R 1 and R 2 Independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl or C1-C50 alkynyl.
[0011] Preferably, the cathode electrochromic material 2 has a structure as shown in formula (II):
[0012]
[0013] Among them, X 2 - Selected from I - Br - , Cl - , ClO 4 - , BF 4 - PF 6 - or TFSI - , R 3 and R 4 Independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl or C1-C50 alkynyl.
[0014] Preferably, the anode electrochromic material has a structure as shown in formula (III):
[0015]
[0016] Among them, R 5 and R 6R is independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl, C1-C50 alkynyl or hydrogen; 7~14 Independently selected from H, F, Cl, Br, I, CN, NO 2 , alkyl, alkoxy, aryl or amino.
[0017] Preferably, the molar ratio of the cathode electrochromic material 1, the cathode electrochromic material 2 and the anode electrochromic material is 6-12:19-26:22-28; the molar volume ratio of the cathode electrochromic material 1 and the electrolyte is 6-12 mmol:4-6 mL; and the electrolyte comprises propylene carbonate and an ionic salt.
[0018] Preferably, the anion in the ionic salt is tetrafluoroborate, perchlorate, hexafluorophosphate or bistrifluoromethanesulfonimide, and the cation is lithium ion, potassium ion, tetrabutylammonium ion or n-butylammonium ion.
[0019] Preferably, the mass ratio of propylene carbonate to ionic salt is 90-98:3-10.
[0020] Preferably, the transparent conductive electrode 1 is composed of a substrate 1 and a transparent conductive layer 1; the transparent conductive electrode 2 is composed of a substrate 2 and a transparent conductive layer 2; the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are independently selected from indium tin oxide, fluorine-doped indium tin oxide or silver nanowires.
[0021] The present invention also provides a method for preparing the transparent-black electrochromic device described above, comprising the following steps:
[0022] (1) mixing cathode electrochromic material 1, cathode electrochromic material 2, anode electrochromic material and electrolyte to obtain a color-changing active material;
[0023] (2) A cavity is formed between the transparent conductive electrode 1 and the transparent conductive electrode 2, and a color-changing active material is injected into the cavity to form a color-changing active layer, thereby obtaining a transparent-black electrochromic device.
[0024] Preferably, in step (2), the thickness of the cavity is 125-150 μm.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention selects appropriate types of cathode / anode electrochromic materials and uses a physical blending method to complement the colors to achieve uniform and full absorption in the visible light region, thereby obtaining a truly black electrochromic device.
[0027] (2) The electrochromic material and the electrolyte material of the present invention together constitute the color-changing active material. An integrated electrochromic device is assembled by a simple vacuum infusion method, which greatly simplifies the structure and processing technology of the electrochromic device.
[0028] (3) The electrochromic device of the present invention can realize the change from transparent to black under different voltages, and the black color is very pure (the color coordinates are L*=22.28, a*=0.45, b*=0.45); in addition, the electrochromic device has excellent cycle stability (attenuation is only ≤5% after 1000 cycles), and has great application prospects in the fields of smart glasses, rearview mirrors, and car skylights. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic structural diagram of the transparent-black electrochromic device of the present invention, wherein 1 is substrate one, 2 is transparent conductive layer one, 3 is color-changing active layer, 4 is substrate two, and 5 is transparent conductive layer two. DETAILED DESCRIPTION
[0030] The present invention provides a transparent-black electrochromic device, which comprises a transparent conductive electrode 1, a color-changing active layer, and a transparent conductive electrode 2 which are arranged in sequence;
[0031] The color-changing active layer comprises a cathode electrochromic material 1, a cathode electrochromic material 2, an anode electrochromic material and an electrolyte.
[0032] In the present invention, the cathode electrochromic material 1 has a structure as shown in formula (I):
[0033]
[0034] Among them, X 1 - Selected from I - Br - , Cl - , ClO 4 - , BF 4 - PF 6 - or TFSI - , R 1 and R 2Independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl or C1-C50 alkynyl. The cathode electrochromic material 1 is a viologen derivative.
[0035] In the present invention, the cathode electrochromic material 2 has a structure as shown in formula (II):
[0036]
[0037] Among them, X 2 - Selected from I - Br - , Cl - , ClO 4 - , BF 4 - PF 6 - or TFSI - , R 3 and R 4 Independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl or C1-C50 alkynyl. The cathode electrochromic material 2 is a diallyl viologen derivative.
[0038] In the present invention, the anode electrochromic material has a structure as shown in formula (III):
[0039]
[0040] Among them, R 5 and R 6 R is independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl, C1-C50 alkynyl or hydrogen; 7~14 Independently selected from H, F, Cl, Br, I, CN, NO 2, alkyl, alkoxy, aryl or amino. The anode electrochromic material is a phenazine derivative.
[0041] In the present invention, the molar ratio of the cathode electrochromic material 1, the cathode electrochromic material 2 and the anode electrochromic material is 6-12:19-26:22-28, preferably 8-11:20-25:23-26, and more preferably 10:22:23; the molar volume ratio of the cathode electrochromic material 1 and the electrolyte is 6-12mmol:4-6mL, preferably 8-11mmol:5mL, and more preferably 10mmol:5mL; the electrolyte comprises propylene carbonate and an ionic salt.
[0042] In the present invention, the anion in the ionic salt is tetrafluoroborate, perchlorate, hexafluorophosphate or bistrifluoromethanesulfonyl imide, preferably perchlorate, and the cation is lithium ion, potassium ion, tetrabutylammonium ion or n-butylammonium ion, preferably lithium ion.
[0043] In the present invention, the mass ratio of propylene carbonate to ionic salt is 90-98:3-10, preferably 92-96:4-8, and more preferably 93-95:5-7.
[0044] In the present invention, the transparent conductive electrode 1 is composed of a substrate 1 and a transparent conductive layer 1; the transparent conductive electrode 2 is composed of a substrate 2 and a transparent conductive layer 2; the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are independently selected from indium tin oxide, fluorine-doped indium tin oxide or silver nanowires, preferably indium tin oxide or fluorine-doped indium tin oxide, and further preferably indium tin oxide.
[0045] In the present invention, the materials of the substrate 1 and the substrate 2 are glass, PET or PDMS.
[0046] The present invention also provides a method for preparing the transparent-black electrochromic device described above, comprising the following steps:
[0047] (1) mixing cathode electrochromic material 1, cathode electrochromic material 2, anode electrochromic material and electrolyte to obtain a color-changing active material;
[0048] (2) A cavity is formed between the transparent conductive electrode 1 and the transparent conductive electrode 2, and a color-changing active material is injected into the cavity to form a color-changing active layer, thereby obtaining a transparent-black electrochromic device.
[0049] In the present invention, the specific process of forming the cavity is preferably: coating the four sides of the transparent conductive layer 2 of the transparent conductive electrode 2 with a thermosetting adhesive, and then covering the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 on the adhesive frame, and then forming a cavity between the transparent conductive electrode 1 and the transparent conductive electrode 2 after curing.
[0050] In the present invention, the curing is preferably UV curing or thermal curing, wherein the UV curing time is 20 to 40 seconds, the thermal curing temperature is 70 to 90° C., and the thermal curing time is 0.5 to 1.5 hours.
[0051] In the present invention, in step (2), the thickness of the cavity is 125-150 μm, preferably 125 μm, 130 μm, 140 μm, or 150 μm.
[0052] In the present invention, in step (2), the color-changing active material is injected into the cavity preferably by vacuum infusion.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] Propylene carbonate and lithium perchlorate are mixed in a mass ratio of 95:5, and ultrasonically treated for 5 minutes to obtain an electrolyte; 10 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-1), 22 mmol of cathode electrochromic material 2 as shown in formula (Ⅱ-1) and 23 mmol of anode electrochromic material as shown in formula (Ⅲ-1) are added to 5 mL of the electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material.
[0056]
[0057]
[0058] The synthesis steps of the cathode electrochromic material 1 shown in formula (I-1) are:
[0059]
[0060] ① Add 2.34 g of 4,4′-bipyridine a, 1.5 g of 5-bromo-1-pentanol and 60 mL of acetonitrile to the reaction bottle in sequence, heat and reflux at 60°C for 12 h. After the reaction is completed, evaporate the acetonitrile using a rotary evaporator, wash the remaining solid with ether to remove residual impurities, collect the solid and dry it in a blast oven for 24 h to obtain the first intermediate product b with a yield of 77.9%.
[0061] ② Add 6.64 g of the first intermediate product b, 2.69 g of 1-bromoheptane and 60 mL of acetonitrile to the reaction bottle in sequence, heat and reflux at 80°C for 24 hours. After the reaction is completed, the brown-yellow precipitate is separated by vacuum filtration, and the solid product is washed with acetonitrile to remove residual impurities. The solid is collected and dried in a blast oven for 24 hours to obtain the second intermediate product c with a yield of 82.2%.
[0062] ③ 1.22 g of the second intermediate product c, 1.1 g of potassium hexafluorophosphate and 80 mL of deionized water were added to the reaction bottle in sequence and placed in an ultrasonic cleaner for 10 minutes. After the reaction was completed, the white precipitate was separated by vacuum filtration, and the solid product was washed with deionized water to remove residual impurities. The solid was collected and dried in a blast oven to obtain the cathode electrochromic material 1 shown in formula (Ⅰ-1), with a yield of 78.2%.
[0063] The synthesis steps of cathode electrochromic material 2 as shown in formula (II-1) are:
[0064]
[0065] ① Add 2.75 g of 1,2-di(4-pyridyl)ethylene d, 5.55 g of 4-methylbenzyl bromide and 50 mL of acetonitrile to the reaction bottle in sequence, heat and reflux at 80°C for 24 h. After the reaction is completed, separate the brown-yellow precipitate by vacuum filtration, and wash the solid product with acetonitrile to remove residual impurities. Collect the solid and dry it in a blast oven for 24 h to obtain the first intermediate product e with a yield of 81.2%.
[0066] ② 1.31 g of the first intermediate product e, 0.64 g of lithium perchlorate and 80 mL of deionized water were added to the reaction bottle in sequence and placed in an ultrasonic cleaner for 10 minutes. After the reaction was completed, the white precipitate was separated by vacuum filtration, and the solid product was washed with deionized water to remove residual impurities. The solid was collected and dried in a blast oven to obtain the cathode electrochromic material 2 shown in (Ⅱ-1), with a yield of 83.5%.
[0067] The synthesis steps of the anode electrochromic material shown in formula (III-1) are:
[0068]
[0069] Dissolve 5.0g of phenyl lithium in 60mL of ether and 9g of phenazine f in 60mL of tetrahydrofuran. Slowly add the ether solution to the tetrahydrofuran solution at room temperature and continue stirring for 0.5h, then add 8.5g of methyl iodide. Stir the brown mixture at room temperature for 2h, then hydrolyze with dilute hydrochloric acid to obtain an oily substance, which is recrystallized from anhydrous ethanol to obtain 7.3g of a mixture. Dissolve the mixture in benzene, separate and purify using an alumina chromatography column, and recrystallize using anhydrous ethanol to obtain 5g of the anode electrochromic material shown in (III-1), with a yield of 37.8%.
[0070] A thermosetting glue is applied around the transparent conductive layer 2 of the transparent conductive electrode 2, and then the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 is covered on the glue frame, wherein the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are indium tin oxide, and the materials of the substrate 1 and the substrate 2 are glass. Then, they are placed in an oven and thermally cured at a temperature of 85°C for 1 hour. The transparent conductive electrode 1 and the transparent conductive electrode 2 are bonded to form a cavity with a thickness of 125μm. Then, the above-mentioned color-changing active material is vacuum-filled into the cavity to form a color-changing active layer, and a transparent-black electrochromic device is obtained.
[0071] Example 2
[0072] The difference from Example 1 is that 6 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-1), 19 mmol of cathode electrochromic material as shown in formula (Ⅱ-1), and 22 mmol of anode electrochromic material as shown in formula (Ⅲ-1) are added to 5 mL of electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material. Other conditions are the same.
[0073] Example 3
[0074] The difference from Example 1 is that 12 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-1), 26 mmol of cathode electrochromic material as shown in formula (Ⅱ-1), and 28 mmol of anode electrochromic material as shown in formula (Ⅲ-1) are added to 5 mL of electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material. Other conditions are the same.
[0075] Example 4
[0076] The difference from Example 1 is that 10 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-1), 23 mmol of cathode electrochromic material as shown in formula (Ⅱ-1), and 26 mmol of anode electrochromic material as shown in formula (Ⅲ-1) are added to 5 mL of electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material. Other conditions are the same.
[0077] Example 5
[0078] The difference from Example 1 is that 9 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-1), 21 mmol of cathode electrochromic material as shown in formula (Ⅱ-1), and 25 mmol of anode electrochromic material as shown in formula (Ⅲ-1) are added to 5 mL of electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material. Other conditions are the same.
[0079] Example 6
[0080] Propylene carbonate and lithium perchlorate are mixed in a mass ratio of 95:5, and ultrasonically treated for 5 minutes to obtain an electrolyte; 10 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-2), 25 mmol of cathode electrochromic material 2 as shown in formula (Ⅱ-2) and 23 mmol of anode electrochromic material as shown in formula (Ⅲ-2) are added to 5 mL of the electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material.
[0081]
[0082] The synthesis steps of the cathode electrochromic material 1 shown in formula (I-2) are:
[0083]
[0084] ① 2.34 g of 4,4′-bipyridine a, 1.36 g of 4-chlorobutyl acetate and 60 mL of acetonitrile were added to the reaction bottle in sequence, and heated under reflux at 60° C. for 12 h. After the reaction was completed, the acetonitrile was evaporated using a rotary evaporator, and the remaining solid was washed with ether to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the first intermediate product b with a yield of 72.8%.
[0085] ② Add 4.41 g of the first intermediate product b, 2.32 g of 1-chloro-3-phenylpropane and 60 mL of acetonitrile to the reaction bottle in sequence, heat and reflux at 80°C for 24 hours. After the reaction is completed, separate the brown-yellow precipitate by vacuum filtration, and wash the solid product with acetonitrile to remove residual impurities. Collect the solid and dry it in a forced air oven for 24 hours to obtain the cathode electrochromic material 1 shown in formula (Ⅰ-2), with a yield of 84.3%.
[0086] The synthesis steps of the cathode electrochromic material 2 shown in formula (II-2) are:
[0087]
[0088] ① 2.75 g of 1,2-di(4-pyridyl)ethylene c, 1.14 g of 5-bromo-2-methyl-2-pentene and 50 mL of acetonitrile were added to the reaction bottle in sequence and refluxed at 60°C for 12 h. After the reaction was completed, the acetonitrile was evaporated using a rotary evaporator, and the remaining solid was washed with ether to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the first intermediate product d with a yield of 74.1%.
[0089] ② 4.0 g of the first intermediate product d, 2.66 g of (4-bromobutyl)cyclopropane and 60 mL of acetonitrile were added to the reaction bottle in sequence and heated under reflux at 80°C for 24 h. After the reaction was completed, the brown-yellow precipitate was separated by vacuum filtration, and the solid product was washed with acetonitrile to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the cathode electrochromic material 2 shown in formula (II-2), with a yield of 84.9%.
[0090] The synthesis steps of the anode electrochromic material shown in formula (III-2) are:
[0091]
[0092] ① Add 1.36g of 5,10-dihydro-2,8-dinitrophenazine e, 0.79g of bromobenzene, 1g of potassium carbonate, 0.2g of tert-butylphosphine tetrafluoroborate and 0.005g of palladium acetate into a double-necked flask, add 60mL of toluene and reflux for 12h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature and add deionized water to quench. Add dichloromethane and saturated brine to the mixed solution for multiple extractions. After the extraction, the organic phase is dried with anhydrous magnesium sulfate to remove water, and the organic phase is separated from magnesium sulfate by vacuum filtration. After adding crude silica gel, use a rotary evaporator to evaporate the solvent, use a thin layer silica gel chromatography column for separation and purification (eluent is dichloromethane / petroleum ether = 1 / 6), and use a rotary evaporator to evaporate the solvent to obtain the first intermediate product f with a yield of 63.8%.
[0093] ② Dissolve 1 g of the first intermediate product f in 40 mL of a mixed solvent (dichloromethane / anhydrous ethanol = 1 / 1), add 0.38 g of sodium borohydride after complete dissolution, and a white precipitate appears in the mixed solution. Separate the white precipitate by vacuum filtration, and wash the solid product with dichloromethane and anhydrous ethanol to remove residual impurities. Collect the solid and dry it in a blast oven for 24 hours to obtain the anode electrochromic material shown in (III-2), with a yield of 82.5%.
[0094] A thermosetting glue is applied around the transparent conductive layer 2 of the transparent conductive electrode 2, and then the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 is covered on the glue frame, wherein the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are indium tin oxide, and the materials of the substrate 1 and the substrate 2 are glass. Then, they are placed in an oven and thermally cured at a temperature of 85°C for 1 hour. The transparent conductive electrode 1 and the transparent conductive electrode 2 are bonded to form a cavity with a thickness of 150μm. Then, the above-mentioned color-changing active material is vacuum-filled into the cavity to form a color-changing active layer, and a transparent-black electrochromic device is obtained.
[0095] Example 7
[0096] Propylene carbonate and lithium perchlorate are mixed in a mass ratio of 95:5, and ultrasonically treated for 5 minutes to obtain an electrolyte; 8 mmol of cathode electrochromic material 1 as shown in formula (Ⅰ-3), 24 mmol of cathode electrochromic material 2 as shown in formula (Ⅱ-3) and 24 mmol of anode electrochromic material as shown in formula (Ⅲ-3) are added to 5 mL of the electrolyte and ultrasonically treated for 10 minutes to obtain a color-changing active material.
[0097]
[0098]
[0099] The synthesis steps of the cathode electrochromic material 1 shown in formula (I-3) are:
[0100]
[0101] ① Add 2.34 g of 4,4′-bipyridine a, 1.49 g of 2-(-3-bromopropyl)ethylene oxide and 60 mL of acetonitrile to the reaction bottle in sequence, heat and reflux at 60°C for 12 h. After the reaction is completed, evaporate the acetonitrile using a rotary evaporator, wash the remaining solid with ether to remove residual impurities, collect the solid and dry it in a blast oven for 24 h to obtain the first intermediate product b with a yield of 74.4%.
[0102] ② 3.62 g of the first intermediate product b, 2.01 g of bromobutane and 60 mL of acetonitrile were added to the reaction bottle in sequence and heated under reflux at 80°C for 24 h. After the reaction was completed, the brown-yellow precipitate was separated by vacuum filtration, and the solid product was washed with acetonitrile to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the second intermediate product c with a yield of 85.7%.
[0103] ③ 1.15 g of the second intermediate product c, 0.56 g of lithium tetrafluoroborate and 80 mL of deionized water were added to the reaction bottle in sequence and placed in an ultrasonic cleaner for 10 minutes. After the reaction was completed, the white precipitate was separated by vacuum filtration, and the solid product was washed with deionized water to remove residual impurities. The solid was collected and dried in a blast oven to obtain the cathode electrochromic material 1 shown in (Ⅰ-3), with a yield of 71.2%.
[0104] The synthesis steps of cathode electrochromic material 2 as shown in formula (II-3) are:
[0105]
[0106] ① 2.75 g of 1,2-di(4-pyridyl)ethylene d, 1.22 g of 4-bromo-1-butene and 50 mL of acetonitrile were added to the reaction bottle in sequence and heated under reflux at 60°C for 12 h. After the reaction was completed, the acetonitrile was evaporated using a rotary evaporator, and the remaining solid was washed with ether to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the first intermediate product e with a yield of 75.6%.
[0107] ② 4.78 g of the first intermediate product e, 3.0 g of 1-bromo-3-phenylpropane and 60 mL of acetonitrile were added to the reaction bottle in sequence and heated under reflux at 80°C for 24 h. After the reaction was completed, the brown-yellow precipitate was separated by vacuum filtration, and the solid product was washed with acetonitrile to remove residual impurities. The solid was collected and dried in a blast oven for 24 h to obtain the second intermediate product f with a yield of 86.9%.
[0108] ③ 1.30 g of the second intermediate product f, 1.72 g of lithium bis(trifluoromethanesulfonyl)imide and 80 mL of deionized water were added to the reaction bottle in sequence and placed in an ultrasonic cleaner for 10 minutes. After the reaction, the white precipitate was separated by vacuum filtration, and the solid product was washed with deionized water to remove residual impurities. The solid was collected and dried in a blast oven to obtain the cathode electrochromic material 2 shown in (Ⅱ-3), with a yield of 75.2%.
[0109] The synthesis steps of the anode electrochromic material shown in formula (III-3) are:
[0110]
[0111] 1.70g of 2,7-dibromo-5,10-dihydrophenazine, 0.79g of bromobenzene, 1g of potassium carbonate, 0.2g of tert-butylphosphine tetrafluoroborate and 0.005g of palladium acetate were added to a double-necked flask, and 60mL of toluene was added to react under nitrogen atmosphere and refluxed for 12h. After the reaction was completed, it was cooled to room temperature and quenched by adding deionized water. Dichloromethane and saturated brine were added to the mixed solution for multiple extractions. After the extraction, the organic phase was dried with anhydrous magnesium sulfate to remove water, and the organic phase was separated from magnesium sulfate by vacuum filtration. Finally, crude silica gel was added and the solvent was removed by rotary evaporation, and a thin layer silica gel chromatography column was used for separation and purification (eluent was dichloromethane / petroleum ether = 1 / 4). After the solvent was rotary evaporated, the anode electrochromic material shown in (Ⅲ-3) was obtained with a yield of 67.8%.
[0112] A thermosetting glue is applied around the transparent conductive layer 2 of the transparent conductive electrode 2, and then the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 is covered on the glue frame, wherein the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are indium tin oxide, and the materials of the substrate 1 and the substrate 2 are glass. Then, they are placed in an oven and thermally cured at a temperature of 85°C for 1 hour. The transparent conductive electrode 1 and the transparent conductive electrode 2 are bonded to form a cavity with a thickness of 130 μm. Then, the above-mentioned color-changing active material is vacuum-filled into the cavity to form a color-changing active layer, and a transparent-black electrochromic device is obtained.
[0113] Comparative Example 1
[0114] The difference from Example 1 is that potassium hexafluorophosphate is used to replace lithium perchlorate, and other conditions are the same.
[0115] Comparative Example 2
[0116] The difference from Example 1 is that tetrabutylammonium hexafluorophosphate is used to replace lithium perchlorate, and other conditions are the same.
[0117] Comparative Example 3
[0118] The difference from Example 1 is that lithium bis(trifluoromethanesulfonyl)imide is used to replace lithium perchlorate, and other conditions are the same.
[0119] The color coordinates of the electrochromic devices of Examples 1 to 7 and Comparative Examples 1 to 3 were detected by using an electrochemical workstation and a colorimeter in combination, and the electrochemical workstation was set to a constant potential mode for testing.
[0120] The test results of Example 1 are shown in Table 1. When the voltage is 1.2V, its L * The value is 22.28, a * is 0.45, b * is 0.45, and its a * 、b * It is very close to 0, proving that there is basically no color difference in the fully colored state.
[0121] The cyclic stability of the electrochromic devices of Examples 1 to 7 and Comparative Examples 1 to 3 was detected by combining an electrochemical workstation with an ultraviolet-visible photometer. The ultraviolet-visible photometer was set to spectral dynamics and the wavelength was set to 550 nm. The electrochemical workstation was set to a multi-potential step mode: the initial potential was 0 V, the termination potential was 1.2 V, the potential pulse width was 70 s, the scanning time was 70000 s, and after 1000 cycles, the optical contrast of the electrochromic device at 550 nm was recorded. The ratio of the optical contrast to the initial optical contrast was the cyclic stability of the device.
[0122] Table 1 Test results of electrochromic devices of Examples 1 to 7 and Comparative Examples 1 to 3
[0123]
[0124] From Table 1, we can see that the ratio of the three color-changing materials is very important. Different ratios will lead to different colors in the device coloring state, and the color difference is characterized by the color coordinate test. * 、b * The closer the value is to 0, the closer the color is to gray-black. From comparative examples 1 to 3, it can be seen that the ionic salt has basically no effect on the color of the system, but has a great impact on the stability of the electrochromic device, so it is very important to control the ratio of the three color-changing materials and the type of ionic salt used.
[0125] As can be seen from the above embodiments, the present invention provides a transparent-black electrochromic device and a preparation method thereof. The transparent-black electrochromic device of the present invention comprises a transparent conductive electrode 1, a color-changing active layer, and a transparent conductive electrode 2; wherein the color-changing active layer comprises a cathode electrochromic material 1, a cathode electrochromic material 2, an anode electrochromic material, and an electrolyte. The present invention selects suitable types of cathode / anode electrochromic materials, and uses a physical blending method to achieve color complementarity and uniform full absorption in the visible light region, thereby obtaining a truly transparent-black electrochromic device.
[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A transparent-black electrochromic device, characterized in that: The transparent-black electrochromic device comprises a transparent conductive electrode 1, a color-changing active layer, and a transparent conductive electrode 2 arranged in sequence; The color-changing active layer comprises a cathode electrochromic material 1, a cathode electrochromic material 2, an anode electrochromic material and an electrolyte.
2. The transparent-black electrochromic device according to claim 1, characterized in that: The cathode electrochromic material 1 has a structure as shown in formula (I): Among them, X1 - Selected from I-, Br - , Cl - 、ClO4 - 、BF4 - PF6 - or TFSI - , R1 and R2 are independently selected from C1~C50 alkyl, C1~C50 cycloalkyl, C1~C50 polycycloalkyl, C1~C50 heterocycloalkyl, C1~C50 aryl, C1~C50 alkaryl, C1~C50 aralkyl, C1~C50 alkoxy, C1~C50 ester, C1~C50 hydroxy, C1~C50 alkenyl or C1~C50 alkynyl.
3. The transparent-black electrochromic device according to claim 1 or 2, characterized in that: The cathode electrochromic material 2 has a structure as shown in formula (II): Among them, X2 - Selected from I - Br - , Cl - 、ClO4 - 、BF4 - PF6 - or TFSI - , R3 and R4 are independently selected from C1~C50 alkyl, C1~C50 cycloalkyl, C1~C50 polycycloalkyl, C1~C50 heterocycloalkyl, C1~C50 aryl, C1~C50 alkaryl, C1~C50 aralkyl, C1~C50 alkoxy, C1~C50 ester, C1~C50 hydroxy, C1~C50 alkenyl or C1~C50 alkynyl.
4. The transparent-black electrochromic device according to claim 3, characterized in that: The anode electrochromic material has a structure as shown in formula (III): wherein R5 and R6 are independently selected from C1-C50 alkyl, C1-C50 cycloalkyl, C1-C50 polycycloalkyl, C1-C50 heterocycloalkyl, C1-C50 aryl, C1-C50 alkaryl, C1-C50 aralkyl, C1-C50 alkoxy, C1-C50 ester, C1-C50 hydroxy, C1-C50 alkenyl, C1-C50 alkynyl or hydrogen; R 7~14 Independently selected from H, F, Cl, Br, I, CN, NO2, alkyl, alkoxy, aryl or amino.
5. The transparent-black electrochromic device according to claim 1, 2 or 4, characterized in that: The molar ratio of the cathode electrochromic material 1, the cathode electrochromic material 2 and the anode electrochromic material is 6-12:19-26:22-28; the molar volume ratio of the cathode electrochromic material 1 and the electrolyte is 6-12 mmol:4-6 mL; and the electrolyte comprises propylene carbonate and an ionic salt.
6. The transparent-black electrochromic device according to claim 5, characterized in that: The anion in the ionic salt is tetrafluoroborate, perchlorate, hexafluorophosphate or bistrifluoromethanesulfonimide, and the cation is lithium, potassium, tetrabutylammonium or n-butylammonium.
7. The transparent-black electrochromic device according to claim 6, characterized in that: The mass ratio of the propylene carbonate to the ionic salt is 90-98:3-10.
8. The transparent-black electrochromic device according to claim 6 or 7, characterized in that: The transparent conductive electrode 1 is composed of a substrate 1 and a transparent conductive layer 1; the transparent conductive electrode 2 is composed of a substrate 2 and a transparent conductive layer 2; the materials of the transparent conductive layer 1 and the transparent conductive layer 2 are independently selected from indium tin oxide, fluorine-doped indium tin oxide or silver nanowires.
9. The method for preparing a transparent-black electrochromic device according to any one of claims 1 to 8, characterized in that: The steps include: (1) mixing cathode electrochromic material 1, cathode electrochromic material 2, anode electrochromic material and electrolyte to obtain a color-changing active material; (2) A cavity is formed between the transparent conductive electrode 1 and the transparent conductive electrode 2, and a color-changing active material is injected into the cavity to form a color-changing active layer, thereby obtaining a transparent-black electrochromic device.
10. The preparation method according to claim 9, characterized in that: In the step (2), the thickness of the cavity is 125 to 150 μm.
Citation Information
Patent Citations
Conjugated expanded viologen derivative as well as preparation method and application thereof
CN102942517A
Electrochromic material and electrochromic device
CN103045228A
Preparation method of novel fast-response high-contrast electrochromic device
CN104216192A
Electrochromic conductive polymer composite film and device preparation method
CN112552896A
Transparent-black photocuring electrochromic device as well as preparation method and application thereof
CN116909067A
Cited By
Electrochromic composition capable of completely fading and application thereof
CN120590933A